The Effect of Socio-Economic of Family and Future Orientation Through Self-Motivation Towards the Interest in Continuing to the College of the Twelfth Grade Students of State Senior High Schools in Brebes Regency - MF, Nur Hanifah; Rusdarti, Rusdarti; Pujiati, Amin (Universitas Negeri Semarang, 2018)
Higher education is held to prepare students to have the academic and professional ability to improve quality. The aims of this study is to analyze the effect of socioeconomic of family and future orientation toward the interest in continuing to the college through the self-motivation. The study used a survey research design and cross section study. The population was 5,247 students, with proportional cluster random sampling technique obtained by the sample size of 372 students. The technique of data collection by using questionnaires. Data analysis used path test and sobel test. The results shows that there is a direct effect of socioeconomic of family towards the interest to the college is 9.5% and a total influence of socioeconomic towards interest to the college through self- motivation is 12.3%, the direct effect on future orientation towards the interest to the collegeis 10% and total effect on future orientation towards the interest to the college through self-motivation is 25.8%. The total effect is greater than the direct effect, so there is a mediation between the socioeconomic of family and future orientation towards the interest to the college.